Large conductance Ca2+‐activated K+ (BK) channels promote secretagogue‐induced transition from spiking to bursting in murine anterior pituitary corticotrophs. (23rd January 2015) - Duncan, Peter J.; Şengül, Sevgi; Tabak, Joël; Ruth, Peter; Bertram, Richard; Shipston, Michael J.
Abstract : Key points: Corticotroph cells of the anterior pituitary are electrically excitable and are an integral component of the hypothalamic‐pituitary‐adrenal axis which governs the neuroendocrine response to stress. Corticotrophs display predominantly single spike activity under basal conditions that transition to complex bursting behaviours upon stimulation by the hypothalamic secretagogues corticotrophin‐releasing hormone (CRH) and arginine vasopressin (AVP); however, the underlying mechanisms controlling bursting are unknown. In this study, we show that CRH and AVP induce different patterns of corticotroph electrical activity, and we use an electrophysiological approach combined with mathematical modelling to show the ionic mechanisms for these differential effects. The data reveal that secretagogue‐induced bursting is dependent on large conductance Ca 2+ ‐activated K + (BK) channels and is driven primarily by CRH whereas AVP promotes an increase in single‐spike frequency through BK‐independent pathways involving activation of non‐selective cation conductances. As corticotroph excitability is differentially regulated by CRH and AVP this may allow corticotrophs to respond appropriately to different stressors. Abstract: Anterior pituitary corticotroph cells are a central component of the hypothalamic‐pituitary‐adrenal (HPA) axis essential for the neuroendocrine response to stress. Corticotrophs are excitable cells that receive input from two hypothalamic secretagogues, corticotrophin‐releasing hormone (CRH) and arginine vasopressin (AVP) to control the release of adrenocorticotrophic hormone (ACTH). Although corticotrophs are spontaneously active and increase in excitability in response to CRH and AVP the patterns of electrical excitability and underlying ionic conductances are poorly understood. In this study, we have used electrophysiological, pharmacological and genetic approaches coupled with mathematical modelling to investigate whether CRH and AVP promote distinct patterns of electrical excitability and to interrogate the role of large conductance calcium‐ and voltage‐activated potassium (BK) channels in spontaneous and secretagogue‐induced activity. We reveal that BK channels do not play a significant role in the generation of spontaneous activity but are critical for the transition to bursting in response to CRH. In contrast, AVP promotes an increase in single spike frequency, a mechanism independent of BK channels but dependent on background non‐selective conductances. Co‐stimulation with CRH and AVP results in complex patterns of excitability including increases in both single spike frequency and bursting. The ability of corticotroph excitability to be differentially regulated by hypothalamic secretagogues provides a mechanism for differential control of corticotroph excitability in response to different stressors.